Description Of Leukocytes And Thoracic X-Ray In Children With Covid-19 At Bunda Thamrin Hospital Medan For The Period March 2020-May 2021 - Chairunnisa Karim Chan; Eka Airlangga (Journal Of Social Science (JoSS), 2023)
COVID-19 has been declared a public health emergency of international concern by WHO on January 30, 2020. The number of cases of COVID-19 in the world is increasing every year. The COVID-19 virus, apart from attacking adults, can also attack children. Clinical manifestations that arise in infected children range from asymptomatic to severe symptoms. Laboratory examinations such as leukocytes and chest x-ray are important examinations and the first step that can be done in children with positive COVID-19 and suspected COVID-19. To determine the description of leukocytes and chest x-ray examination in children with COVID-19 at Bunda Thamrin Hospital, Medan from March 2020 to May 2021. The design of this study was a descriptive observational study with a cross sectional method. The samples used in this study amounted to 134 samples. Data collection was carried out with secondary data, where data was taken on the first day the child was treated for COVID-19, this data was obtained from the results of medical records at Bunda Thamrin Hospital in Medan, then the data was collected for data analysis. from 134 samples obtained normal leukocyte values were 120 people (89.6%), leukopenia were 8 people (6%) and leukocytosis was 6 people (4.5%).